Implementasi Sensor Getar dan PIR untuk Alat Pengaman Mobil Berbasis Internet of Things - roza susanti (Elektron : Jurnal Ilmiah, 2021)
The era of technology is developing rapidly along with the needs, various problems that arise can be overcome with technology. Internet Of Things (IOT) based car vehicle security system, using the NodeMCU ESP8266 microcontroller and a smartphone equipped with emergency safety features with accuracy and precision that support the realization of an interactive security system. This research starts from making the physical form of a car safety device with a control system using a microcontroller, programming the microcontroller and measuring system performance. Based on the test, it can be concluded, where this tool can function properly by combining hardware and software, namely the response time of the MCU Node sending messages to the owner's cellphone via telegram is 5.88 seconds. The security system can be monitored in real time without any distance limitations.